2022
DOI: 10.28945/5020
|View full text |Cite
|
Sign up to set email alerts
|

The Effort-Reward-Imbalance Among PhD Students – A Qualitative Study

Abstract: Aim/Purpose: The purpose of this paper is to examine the perceived efforts, rewards, motives, and coping strategies of a sample of PhD students in Germany based on tested stress models, the Effort-Reward-Imbalance Model and the Transactional Model of Stress and Coping. Background: Pursuing a PhD can be challenging and stressful. Students face conflicts, isolation, and competition as well as difficulties with their supervisors. However, there is little known about how students perceive their PhD. Methodology:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Looking at the job demands-resources model, I can point out some of the stressors that cause this ill-being, echoing earlier studies (Mackie & Bates, 2019;Schmidt & Hansson, 2018;Vilser et al, 2022). More than 85% of the participants stated that they do not feel rightly rewarded for their efforts.…”
Section: Job Demands Versus Resourcesmentioning
confidence: 51%
See 1 more Smart Citation
“…Looking at the job demands-resources model, I can point out some of the stressors that cause this ill-being, echoing earlier studies (Mackie & Bates, 2019;Schmidt & Hansson, 2018;Vilser et al, 2022). More than 85% of the participants stated that they do not feel rightly rewarded for their efforts.…”
Section: Job Demands Versus Resourcesmentioning
confidence: 51%
“…Others look at their physical health and advise organizing health labs or fitness classes (Haynes et al, 2012). Ideas to improve their feeling of relatedness include creating networking workshops or mentoring programmes with postdocs (Vilser et al, 2022), writer's groups (Beasy et al, 2020), support groups (Panayidou & Priest, 2021) that help PhD students to connect and exchange their experiences or peer coaching (Fried et al, 2019;Skaniakos & Piirainen, 2019). Mentoring programmes and support groups can also help to tackle workrelated efforts, such as problems with time and project management, as well as with the scientific approach of the project (Vilser et al, 2022).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…While PhD students working at the university bear a heavy load of additional tasks, such as preparing teaching materials and supervising theses, external PhD students or those with a scholarship have tasks that differ significantly. These may include job-related work and volunteer activities, in addition to writing their thesis (Vilser, Rauh, et al, 2022). Summing it up, there are a variety of sociodemographic characteristics and PhD-related elements that influence the perception of efforts and rewards.…”
Section: Discussionmentioning
confidence: 99%
“…PhD students are confronted with extensive efforts—from conducting research and attending classes to teaching and managing administrative responsibilities (Bazrafkan et al, 2016; Vilser, Rauh, et al, 2022). Simultaneously, these students seem to receive little reward for their hard work.…”
mentioning
confidence: 99%
“…Over the past decades, numerous studies have revealed unfavorable working conditions and high levels of stress for PhD students ( Levecque et al, 2017 ; Sverdlik et al, 2018 ; Vilser et al, 2022 ). Hence, PhD students often face precarious working conditions, financial insecurities, lack of time, and challenges in balancing personal and academic commitments ( Goller and Harteis, 2014 ; de Vries, 2020 ).…”
Section: Introductionmentioning
confidence: 99%